Albania : From Isolation Toward Reform - Johnston, R.; Mecagni, Mauro; Nagy, Piroska; Pepper, Roy. (Washington, D.C. : International Monetary Fund, 1992)
This study reviews Albania's historical and political background, as well as economic developments in 1991. It describes the centrally planned economic system up to the onset of reform and analyzes economic performance in the 1980s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet